Anti-Biofilm Forming Activity of Natural Products Extract Punica Granatum L. and Magnifera Indica L - Khursheed, Hadia; Faraz, Naveed; Shafique, Sehrish; Mushtaque, Madiha (Journal of Gandhara Medical and Dental Science, 2023)
OBJECTIVES o evaluate the biofilm activity of Escherichia coli and the anti-biofilm forming activity of Pomegranate peels Punica granatum L. and Mango leafs Mangifera Indica L. extracts against Escherichia coli and their combined synergistic effect using 96 well microtiter plate. METHODOLOGY The study design was a cross-sectional study. The sample size was 150. The samples were collected from patients at PNS Shifa Hospital Karachi. The age group of the individuals included was from 15 to 50 years. The specimens received in the lab were inoculated on CLED agar, Blood agar, and MacConkey’s agar culture plates. Escherichia coli was identified by colony morphology, gram staining, TSI, and further biochemical test analysis. After identification, the samples were processed for biofilm activity on 96 well microtiter plate method and using serial dilution method to assess the anti-biofilm activity of natural product extracts. Patient’s age, gender, and hospital number of patients were recorded on specially designed proforma with ERC approval no 83/2021. RESULTS Among 150 patients, 64% were males, and 36% were females. Overall mean age was (33.79±9.94) and (34.02±10.59) years. 90% of samples showed biofilm formation. We found a significant relationship between culture and examination (p-value 0.000), while no significant association was found between gender (p-value 0.69), age (p-value 0.44) and biofilm formation (p-value 0.57). Anti-biofilm forming activity of pomegranate peel extract against Escherichia coli was (24.46±19.09) with mean and standard deviation. Anti-biofilm forming activity of Mango leaf extract against Escherichia coli was (14.90±9.56). Significant synergistic relation was observed in both extracts, Punica granatum L. and Mango leaf extract Mangifera Indica L. used in combination. CONCLUSION It was concluded that a novel combination of natural product extracts had shown higher effectiveness against the rapid emergence of biofilm-forming pathogens.